Newspaper of the hour, sports movement, football, school sports - Kadim Waheed Nema (Journal of College of Education, 2025)
Iraqi newspapers are among the important documents that chronicle and document historical events, so most academic researchers refer to them as primary sources that talk about past periods and important references for documenting and writing the stages of history.      Akhbar Al-Hour newspaper is one of the sober newspapers that was issued in 1953, and its sports pages were among the important pages that had a great role in spreading sports awareness among the Iraqi masses. It is working to develop sports in Iraq, in addition to that, it has transmitted the most important developments related to developments in sports such as (football, basketball, tennis) and others. As most of Iraq’s schools participated in local competitions inside Iraq and international competitions outside of it, students were able to obtain many prizes. In the same field, the military institution participated in local and international competitions, and a number of soldiers were able to obtain valuable prizes. The newspaper did not stop there, but also contributed to Framing the incidents of the circumstances that occurred in Iraq's participation in the Arab Olympics.
Keywords: Newspaper of the hour; sports movement; football; school sports